The effect of chloroform-extractable secondary metabolites of filamentous fungi on the movement of respiratory tract cilia of one-day-old chicks in vitro - Piecková, E; Jesenská, Z (Folia microbiologica, 1995)
The ciliostatic activity of the chloroform-extractable metabolites of 72 strains of filamentous fungi growing in a liquid medium, on tracheal cilia from 1-d-old chicks in vitro was evaluated. Forty-eight of the investigated strains produced ciliostatic metabolites; 13, 11, 16, and 25% of the strains stopped the movement of cilia after 1, 2, 3, 6 d, respectively. The results are discussed in relationship with chronic bronchitis of people working with mouldy materials, living in mouldy dwellings and with the "sick-building syndrome".
Keywords: dýchací soustava; zvířata; techniky in vitro; Fungi; Animals, Newborn; houby; Humans; Chickens; kur domácí; In Vitro Techniques; lidé; Cilia; syndrom nezdravých budov; novorozená zvířata; Animals; Respiratory System; trachea; mykotoxiny; chloroform; Sick Building Syndrome; cilie; Trachea; Chloroform; Mycotoxins